Ladder Distribution of LAIV Reassortment between Vero Adaption Attenuated Strain and Wide Type Highly Virulent Influenza Virus Strain - liu, ze; Huang, Jinhai; Hui, Gao (International Journal of Innovative Research in Medical Science, 2024)
It described the “ladder distribution” of live attenuated influenza vaccine (LAIV) reassortment between Vero cells adaption attenuated strain and wide type-high virulent influenza virus strains by the reverse genetics approach. That gene constellation could save the immunogenicity (imm) of the parental strain and make new reassort virus strain attenuation (att) characteristics for further vaccine using, rapidly, not only seasonal vaccine but also pandemic flu vaccine.